FAKTOR - FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak Orang Pribadi Di KPP Semarang Barat) - Ayu Ir Sutrisni, 12.05.52.0032; Oktaviani, R. Meita (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the tax administration system, e-filling system, and taxpayer’s awarenes on income tax with tax compliance as intervening. The population in this study is the individual taxpayer in the region of KPP Pratama Semarang Barat. Sampling was done by purposive sampling technique. The number of samples was determined as many as 125 people from the number of individual taxpayers who are on KPP SemarangBarat. Data analysis techniques used in this research is the technique of multiple regression analysis. Finding of this research indicated the tax administration system and e-filling system not influential toward taxpayer compliance, while taxpayer’s awarenes influential toward taxpayer’s compliance.Keywords: Administration System, E-filling System, Taxpayer’s Awarenes, Taxpayer’s Compliance